Economic Analyses of an Alcohol Misconduct Prevention Program in a Military Setting. Issue 1 (1st January 2017) - Li, Tao; Waters, Teresa M.; Kaplan, Erin K.; Kaplan, Cameron M.; Nyarko, Kwame A.; Derefinko, Karen J.; Talcott, Gerald W.; Klesges, Robert C.
ABSTRACT: Objective: The economic burden associated with alcohol misuse, in particular early attrition or discharge associated with alcohol-related incidents (ARIs), is significant in military settings. We assessed the potential economic benefit of a brief alcohol intervention program, the Alcohol Misconduct Prevention Program (AMPP), initially implemented at Joint Base San Antonio-Lackland Technical Training site for the U.S. Air Force (USAF) from October 1, 2010, to December 31, 2012. Methods: We conducted cost-effectiveness and cost–benefit analyses of the AMPP from the perspective of the USAF. Program effectiveness was measured as the number of ARIs avoided after the AMPP implementation, and program benefit was measured as the potential cost savings related to reductions in ARIs. One-way sensitivity analyses were conducted to examine the robustness of base case results. Results: The AMPP resulted in the avoidance of 59 ARIs which cost 9, 869 for every ARI avoided. For every dollar invested in the AMPP, the USAF saved 4.09 in a conservative model without health effects, and saved 6.17 taking into account the potential health benefits. Our findings of favorable cost benefit were robust across sensitivity analyses. Conclusions: Investing in the AMPP at other military bases is likely to produce substantial economic benefit.